Cloning and expression of maltooligosyltrehalose trehalohydrolase from Sulfolobus solfataricus DSM 1616 in Bacillus subtilis WB800 - Tien Cuong, Nguyen; Thi Hien Trang, Nguyen; Thi Thao, Nguyen; Thanh Hoang, Le; Sy Le Thanh, Nguyen; Thi Anh Tuyet, Nguyen; Manh Dat, Nguyen; Duc Manh, Le; Thi Thanh Huyen, Do; Thi Thu, Nguyen; Thi Trung, Nguyen; Thi Yen, Hoang; et al. (Vietnam Journal of Biotechnology, 2020)
Maltooligosyltrehalose trehalohydrolase (MTHase) is an industrial enzyme for the production of trehalose. A DNA fragment of 1680 bp encoding for MTHase was cloned from Sulfobolus solfataricus DSM 1616 then fused with promoter acoA-amyE already amplified from pMSE3 vector by PCR to generate an expression cassette acoMTH. Afterward the cassette was inserted into pAC7 vector for expression of the gene in Bacillus subtilis WB800 – a conventional expression system. Gene MTH was inserted into the genome of B. subtilis WB800 by cross-exchange event of pAC7 vector with the host genome for expression of high quality and high quantity of extracellular recombinant protein. By crossing-exchange event at 3’amyE-5’amyE, the expressional cassette was integrated into B. subtilis WB800 genome. The expressional cassette was integrated into B. subtilis WB800 genome replacing 3’amyE-5’amyE, hindering the native amylase activity of the host. Expression of expected protein was confirmed by electrophoresis SDS-PAGE. From our results, it indicates that gene MTH was expressed successfully in B. subtilis WB800. After 0.5% acetoin induction for 48 h, the data showed that the protein with a molecular mass of ~64 kDa on SDS-PAGE was expressed. The level of recombinant protein in WBpAacoMTH was increased and reached 2.5%, 15.2% and 21.95%, respectively comparing with native B. subtilis WB800.